Case Report in the Brazilian Context: Cognitive and Behavioral Changes Following an Electric Injury - Almondes, Katie Moraes de; Azevedo, Julianna Pinto de; Santos, Marina Bruxel dos; Soares, Walter Barbalho (Frontiers in Psychiatry, 2021)
Electrical injury is the sequel of an electrical shock. Physical sequelae are most common, but also other symptoms can happen, such as neurological symptoms, psychiatric alteration, and cognitive decline. The repercussion of electrical injury can happen whether or not the head is a point of contact with the electrical current. There are no official diagnostic criteria for cognitive repercussions of electrical injury, which may lead to incorrect diagnostics and confusion with other most frequent causes of dementia, such as Frontotemporal Dementia, pseudodementia, or dementias for reversible causes. In this case report, we describe a right-handed man, aged 56 years old, referred to our service due to behavioral changes and cognitive alterations related to electric shock. The psychiatric team has monitored him, but cognitive deficits have raised doubts about the presence of dementia syndrome. The neuropsychological evaluation revealed severe deficits and loss of functionality, which filled the criteria for major neurocognitive disorder according to the DSM-5. Adding these findings to the patient's history and after a detailed investigation of other causes of dementia, we conclude that this is a possible case of Electrical Injury with strong neuropsychological symptoms. This case report should help clinicians to recognize this condition and its features. We aim to share the importance of recognizing the neuropsychological and psychiatric features of electrical injury, mainly in the Brazilian context.